2021
DOI: 10.1055/a-1578-1800
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of colon capsule endoscopy as pan-endoscopy: From bowel preparation, transit, and rating times to completion rate and patient acceptance

Abstract: Background and study aims Colon capsule endoscopy (CCE) has the potential to explore the entire gastrointestinal tract. The aim of this study was to assess the applicability of CCE as pan-endoscopy. Patients and methods Healthy participants received CCE with bowel preparation (bisacodyl, polyethylene electrolyte glycol (PEG) + ascorbic acid) and booster regimen (metoclopramide, oral sulfate solution (OSS)). For each segment of the gastrointestinal tract, the following quality parameters were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 33 publications
0
28
0
Order By: Relevance
“…A study conducted in 2021 by Vuik et al using PillCam COLON 2 on 451 participants concluded that colon capsule endoscopy (CCE) was safe and had good acceptance among patients [ 26 ]. CCE received a score of 7.8 on a scale of 1-10; additionally, 91.1% of the participants said they would consider having CCE sometime in the future [ 26 ]. Only 6.6% of those polled said that they would tell others to avoid CCE [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…A study conducted in 2021 by Vuik et al using PillCam COLON 2 on 451 participants concluded that colon capsule endoscopy (CCE) was safe and had good acceptance among patients [ 26 ]. CCE received a score of 7.8 on a scale of 1-10; additionally, 91.1% of the participants said they would consider having CCE sometime in the future [ 26 ]. Only 6.6% of those polled said that they would tell others to avoid CCE [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
“…CCE received a score of 7.8 on a scale of 1-10; additionally, 91.1% of the participants said they would consider having CCE sometime in the future [ 26 ]. Only 6.6% of those polled said that they would tell others to avoid CCE [ 26 ]. The most cumbersome element of the CCE process for most participants (89.2%) was bowel preparation, while for others it was the day of the procedure (8%) or stomach issues after the procedure (3%) [ 26 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…
We read with great interest the paper by Vuik et al [1], reporting a single-center experience with application of colon capsule endoscopy as a panendoscopic tool. Both colon capsules and the newer Pill-Cam Crohn's capsule have been used for panendoscopy in several settings.
…”
mentioning
confidence: 99%